Sistem Informasi Perhitungan Presensi Pegawai STMIK AUB Surakarta - Heribertus Ary Setyadi (STIE AUB Surakarta, 2015)
BAU tasks are done regularly every month is made recap employee attendance, both lecturers and employees. Even though there is register attendance by using fingerprint attendance but every month BAU still manually recalculate a legitimate attendance of each employee. Of the types of existing employees, and hours of attendance calculations differ from one another so that employees BAU requires precision to sort attendance constituted under the working hours of each type of existing employees. BAU also have to look at the data of employees who get a letter of assignment or license in question to add presence that is not stored in the attendance machine. In this research has created a system to help employees BAU in calculating the amount of the legitimate presence of all employees based on the applicable rules and the presence of data taken from the fingerprint machine that already exists. Needs analysis system consists of the functional and non-functional requirements, phase analysis using the system flaws PIECES analysis. This system design using use case diagrams, class diagrams, activity diagrams. Input and output design made to serve as a basis for making a form using Visual Basic. Design database contains an pegawai table, table jam, Table ijin, hitung tables, table rekap and relationships between tables. In the system created can enter employee data that permits or is a task which is attached the official letter. Of rules and data entered license or assignment can generate a list of employee presence and validity of the information on Presence do. The system can also generate a recap of the number of legitimate presence of all employees are used as the basis for calculating the attendance.Keywords : Informationn System, Presence Attendance, Visual Basic, STMIK AUB Surakarta.